A Characterization of Properly Minimal Elements of a Set - Jahn, Johannes (SIAM Journal on Control and Optimization, 1985)
In this paper properly minimal elements of a set are characterized as minimal solutions of appropriate approximation problems without any convexity assumptions.
UnivIS-Import:2015-03-05:Pub.1985.nat.dma.pama21.achara